1995
DOI: 10.1021/bi00043a008
|View full text |Cite
|
Sign up to set email alerts
|

Major Groove (R)-.alpha.-(N6-Adenyl)styrene Oxide Adducts in an Oligodeoxynucleotide Containing the Human n-ras Codon 61 Sequence: Conformations of the R(61,2) and R(61,3) Sequence Isomers from 1H NMR

Abstract: Conformations of (R)-alpha-(N6-adenyl)styrene oxide adducts at positions X6 in d(CGGACXAGAAG).d(CTTCTTGTCCG) and X7 in d(CGGACAXGAAG).d(CTTCTTGTCCG), incorporating codons 60, 61 (underlined), and 62 of the human n-ras protooncogene, were refined from 1H NMR data. These were the R(61,2) and R(61,3) adducts. Chemical shift perturbations were in the 5'-direction from the sites of adduction; large changes were observed for C5 H5 and H6 in the R(61,2) adduct. The styrene moieties were only partially defined by NOE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 76 publications
3
65
0
Order By: Relevance
“…The methods for the chemical synthesis of these unique lesions has been described elsewhere (23,24). The solution structure of the R-and S-SO lesions within an oligodeoxynucleotide duplex revealed that the adducts, which lie in the major groove, are well accommodated by the DNA duplex and do not distort the local helix geometry (21,22). However, the R-and S-SO stereoisomers differ in their spatial orientation; the R-SO N 6 -adenine adduct is directed toward the 5Ј-end of the template (21), whereas the S-SO adduct is directed toward the 3Ј-terminus of the template (22).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methods for the chemical synthesis of these unique lesions has been described elsewhere (23,24). The solution structure of the R-and S-SO lesions within an oligodeoxynucleotide duplex revealed that the adducts, which lie in the major groove, are well accommodated by the DNA duplex and do not distort the local helix geometry (21,22). However, the R-and S-SO stereoisomers differ in their spatial orientation; the R-SO N 6 -adenine adduct is directed toward the 5Ј-end of the template (21), whereas the S-SO adduct is directed toward the 3Ј-terminus of the template (22).…”
Section: Resultsmentioning
confidence: 99%
“…The SO lesions used in this study are known to lie in the major groove without causing a significant perturbation to the local DNA structure (21,22). In contrast, DNA binding by RT is predominantly through the DNA minor groove and RT is unable to bypass R-or S-SO lesions situated in the DNA minor groove (34).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations